Pengaruh Model Pembelajaran Cooperative Integrated Reading Composition Terhadap Kemampuan Membaca Pemahaman Teks Eksposisi Siswa Kelas X SMAN 2 Kota Sukabumi - Salsabila, Nazla; Supendi, Deden Ahmad; Humaira, Hera Wahdah (Peneliti.net, 2025)
This research was motivated by problems with students' ability to understand reading which was still relatively low. An effort to overcome this is by using a learning model that can help improve reading comprehension skills, namely the cooperative integrated reading and composition (CIRC) learning model. This research aims to determine the effect of the CIRC learning model on the ability to read and understand expository texts of class X students at SMAN 2 Sukabumi City before and after being given treatment. This research method uses quantitative pre-experimental research design with a One-Group Pretest Posttest design. The research instrument used pretest-posttest questions in the form of description questions and the sample from this research was class X-J, totaling 31 students. The research results obtained from the average posttest score were 75.10 while the pretest score was 53.03. Apart from that, the t-test results also show that tcount 14.51 is greater than ttable 2.042. Thus, Ha is accepted to show that the CIRC learning model has an effect on the ability to read and understand expository texts in class X-J of SMAN 2 Sukabumi City.